REHABILITASI TERHADAP PENYALAHGUNAAN NARKOTIKA DI TINJAU DARI SISTEM PEMIDANAAN INDONESIA - Syafruddin Syafruddin (Universitas Borneo Tarakan, 2020)
ABSTRACT This research is motivated by the increasingly widespread use of narcotic in Indonesia, while the illegal use of narcotics can be viewed as a crime that can be imposed criminal sanctions in accordance with the provisions of Law of 35 of 2009. This narcotic law, in the case of punishment to the narcotic user, adheres to double track system, namely repressive sanction and action sanction. Medical rehabilitation is one of the framework of action sanction. On that basis, this research refers to two objectives: Analyzing the existence of rehabilitation for narcotic user in the perspective of the Indonesian punishment system and Analyzing the consequences for rehabilitation in cases of narcotic crime.This research is a legal research with normative law research type. The analytical approach uses a statutory approach and a conceptual approach. Sources of legal materials used in this study are primary and secondary legal materials. Primary sources of law relate to written legal products and secular sources of law covering other relevant literature.The results of research show that the existence of rehabilitation for narcotic user in the perspective of the Indonesian punishment system, is basically one of the forms of sanction which must be undertaken by the user of narcotic who is not the category of dealer, because the philosophy of Law of 35 on 2009 on Narcotic adheres to double track system in the case of sanction for the narcotic user, namely a repressive witness and action sanction, so it can be argued that rehabilitation is a manifestation of the sanction of such action. Furthermore, the determination of rehabilitation for narcotic user based on a judge's ruling may have consequences for drug user to undergo medical rehabilitation as a duty.. Furthermore, the role of government is very important through the National Narcotics Agency (BNN) to streamline community participation in the framework of medical rehabilitation and social rehabilitation procedures that are very urgent for the recovery of health and mental recovery of those who have become victims of narcotics. Keywords : Rehabilitation, Criminal Sanction, and Narcotic User